Ground deformation and associated hazards in NW peloponnese (Greece). Issue 1 (1st January 2018) - Del Soldato, Matteo; Del Ventisette, Chiara; Raspini, Federico; Righini, Gaia; Pancioli, Valeria; Moretti, Sandro
ABSTRACT: In the last decades, ground deformations were investigated, analysed and monitored using several methods. As a consequence of a spreading urbanization, several phenomena, e.g. landslide and subsidence, were emphasized or triggered causing not only socio-economic damages, but, in some cases, also casualties. The investigation and mapping of these phenomena are important for both local authorities and civil protection in order to promote a higher conscientious urban planning and to highlight the more hazardous areas. Furthermore, the information are a key point for social development connected to the awareness of the environment and the related risk. The Achaia prefecture, in the north-eastern Peloponnese (Greece), close to the Gulf of Patras, is an area strongly affected by subsidence and landslides. Furthermore, this is an earthquake-prone area, a factor that can trigger some mass movements. For this region, a landslide inventory was realized with the help of the interpretation of Persistent Scatterers data, for the period 1992–2008, and high-resolution optical satellite images, available until 2016, in addition to the investigation of the landslide State of Activity. Moreover, for the coastal area, a section was investigated to evidence subsidence.